Quantitative Immunoblotting of Plasma and Platelet Protein S - Schwarz, H Peter; Heeb, Mary Jo; Lämmle, Bernhard; Berrettini, Mauro; Griffin, John H (Thrombosis and Haemostasis, 1986)
Protein S, the activated protein C cofactor, was measured in plasma and in platelets by a quantitative immunoblotting assay using a double antibody technique. Either whole plasma or platelet lysates were electrophoresed on sodium dodecyl sulfate polyacrylamide gels and transferred to nitrocellulose membranes by electroblotting. Based on the demonstration of proportional transfer of protein S from the gel to the nitrocellulose membrane, a reproducible and sensitive quantitative assay for protein S antigen (∼ 70,000 MW) was developed that correlated well with the Laurell rocket assay for plasma protein S. Pooled normal plasma contains 22 μg/ml protein S. Total platelet protein S antigen at ∼ 70,000 MW was determined in gel filtered platelets of ten healthy adults (mean, 163 ng per 1088 platelets). In the supernatants of thrombin-stimulated platelets, 63% of the total platelet protein S antigen was measured. Thus, quantitative immunoblotting is a useful method to detect low levels of protein S in platelets or in plasma with the advantage of giving qualitative information, i.e. apparent MW, of protein S.
Keywords: Protein S; Platelets; Immunoblotting; Protein C